A microRNA signature of toxic extrasynaptic N-methyl-D-aspartate (NMDA) receptor signaling - Bas Orth, Carlos; Koch, Mirja; Lau, David; Buchthal, Bettina; Bading, Hilmar (Molecular brain, 2020)
The cellular consequences of N-Methyl-D-Aspartate receptor (NMDAR) stimulation depend on the receptors’ subcellular localization. Synaptic NMDARs promote plasticity and survival whereas extrasynaptic NMDARs mediate excitotoxicity and contribute to cell death in neurodegenerative diseases. The mechanisms that couple activation of extrasynaptic NMDARs to cell death remain incompletely understood. We here show that activation of extrasynaptic NMDARs by bath application of NMDA or L-glutamate leads to the upregulation of a group of 19 microRNAs in cultured mouse hippocampal neurons. In contrast, none of these microRNAs is induced upon stimulation of synaptic activity. Increased microRNA expression depends on the pri-miRNA processing enzyme Drosha, but not on de novo gene transcription. These findings suggest that toxic NMDAR signaling involves changes in the expression levels of particular microRNAs.